Analisis Kualitas Soal Evaluasi pada Buku Ajar PAI dan Budi Pekerti SMKN 3 Kota Serang - Siti Ina Mulyani; Umi Syahidah; Salsabila Oktavia; Saefudin Zuhri; Wahyu Hidayat (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research investigates the quality of evaluation questions in the Islamic Religious Education (PAI) and Character Education textbook for vocational high school (SMK) Grade X at SMKN 3 Kota Serang. The analysis focuses on validity, reliability, difficulty level, and discriminating power. The study employed a quantitative descriptive approach, using data collected from the responses of Grade X Accounting students to the evaluation questions provided in the textbook. Findings revealed that, among the 10 questions analyzed, 8 were highly valid, while 2 lacked validity. The reliability of the questions was rated high, with a KR-20 score of 0.74. Regarding difficulty levels, 6 questions were categorized as easy, 4 as moderate, and none as difficult. In terms of discriminating power, 5 questions were classified as excellent, 3 as fair and needing improvement, and 2 as poor and unsuitable for further use. These results highlight the need to revise invalid questions and those with low discriminating power. Additionally, incorporating more challenging questions is recommended to foster students' critical thinking skills. Such measures are critical to enhancing the effectiveness of evaluation questions in assessing students’ capabilities comprehensively.